1993
DOI: 10.1021/ja00059a076
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the gas-phase reaction of trimethylsilyl radicals with hydrogen bromide: measurement of the trimethylsilyl-hydrogen bond strength

Abstract: In a control experiment we also measured the CIDNP of deoxygenated solutions of DMUM (100 mM) and 2MInd (25 mM) in acetonitrile. The spectra are shown in Figure 2. DMUM shows emission at 3.26 and 3.34 ppm due to the two methyl groups at N 3 and N1, respectively, and enhanced absorptions at 7.37 ppm for the proton a t C6. 2MInd shows again enhanced absorption at 2.46 ppm and, in addition, emission at 6.19 ppm for the proton at C3, as well as weak emission and absorption for the aromatic protons. The phases can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…11,39 This value is also very close to one calculated by Allendorf and Mellius 36 from a theoretical ab initio study (BAC-MP4 (STDQ) method). Finally, our value is in agreement with the 16.4 ( 6.0 kJ/mol, reported by Marshall and co-workers, 7,8,40 in which the forward and reverse rate measurements of the Me 3 Si + HBr Me 3 SiH + Br • reaction were measured over a broad temperature range. The trimethylsilyl radical heat of formation was thus determined from the directly measured heat of reaction.…”
Section: B Dissociation Of Me 6 Si 2 (Hmds) Thermochemistry Of the Tr...supporting
confidence: 92%
“…11,39 This value is also very close to one calculated by Allendorf and Mellius 36 from a theoretical ab initio study (BAC-MP4 (STDQ) method). Finally, our value is in agreement with the 16.4 ( 6.0 kJ/mol, reported by Marshall and co-workers, 7,8,40 in which the forward and reverse rate measurements of the Me 3 Si + HBr Me 3 SiH + Br • reaction were measured over a broad temperature range. The trimethylsilyl radical heat of formation was thus determined from the directly measured heat of reaction.…”
Section: B Dissociation Of Me 6 Si 2 (Hmds) Thermochemistry Of the Tr...supporting
confidence: 92%
“…FP-RF37 and DF-MS38 experiments yielded jk9(7) = (5.1 ± 0.7) X 1(F" exp(-2900 ± 70 K/T) and (4.0 ± 0.3) X 10-" exp(-2640 ± 260 K/T) cm3 molecule-' s-', respectively. A reasonable assumption is fclb = kg, so that fclb(n = 4.6X 10"11 X exp(-2770 K/T) cm3 molecule-1 s-1 (10) A second way to analyze channel lb is via investigation of the reaction of oxygen atoms with trimethylchlorosilane. H-atom abstraction from an Si-H bond is blocked because the Si-H bond of trimethylsilane is replaced by an Si-Cl bond in trimethylchlorosilane.…”
Section: Discussionmentioning
confidence: 99%
“…The enthalpy change for reaction 3 (R = H) is also estimated to be 383 kJ mol-1 at the CISD+SCC/6-31G** level of theory. 2 Marshall and co-workers,26 on the basis of kinetic observations, questioned the early conclusions that successive Me substitution produces no change in Si-H bond strength, and studied the kinetics of reaction 6 for R = Me in order to obtain the bond dissociation enthalpy D°(Me3Si-H).12'26 27 Combination of the activation energies of forward26 and reverse12,27 reactions yields D°298(Me3Si-H) = 397.4 ± 2.0 kJ mol-1 and AHf^slMesSiO = 16.4 ± 6.0 kJ mol-1. Similar results have been obtained from an independent kinetic study on the very low pressure pyrolysis of hexamethyldisilane, giving a bond dissociation enthalpy Z3°29s(Me3Si-SiMe3) = 332 ± 12 kJ mol-1.…”
Section: B Thermodynamic Datamentioning
confidence: 99%
“…f-BuOCV-Bu 130 °C (Me3Si)3Si-Si(SiMe3)3 (27) The kinetics of the reactions of silyl radicals with carbon-centered radicals have recently attracted attention. In particular, the Arrhenius parameters for the reactions of the methyl radical with H3Si*, Cl3-Si*, and Me3Si* radicals were measured in the gas phase.141 Studies on the steady-state and the pulse radiolysis of Et3SiH in methanol showed that the reactions 28 and 29, play an important role in this system, occurring with rate constants of 1.1 x 108 and 0.7 x 108 M"1 s"1, respectively.142…”
Section: (Me3si)3sihmentioning
confidence: 99%